2018
DOI: 10.1371/journal.pone.0199170
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants and health outcome variation in individuals with type 1 diabetes mellitus: A register-based study

Abstract: BackgroundSocioeconomic status, origin or demographic attributes shall not determine the quality of healthcare delivery, according to e.g. United Nations and European Union rules. Health equity has been defined as the absence of systematic disparities and unwarranted differences between groups defined by differences in social advantages. A study was performed to investigate whether this was applicable to type 1 diabetes mellitus (T1D) care in a setting with universal, tax-funded healthcare.MethodsThis retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Our finding of higher HbA1c levels among younger age groups have similarly been reported in earlier registry reports. 11,19,20 One of the unique elements in this registry is that each endocrinologist receives a quarterly report outlining their patient populations' achievements in metabolic outcomes, expressed both as means and as centile ranking within the group, along with the proportion using evidence-based cardiovascular disease prevention therapies. In other jurisdictions, 21 quality improvement initiatives have similarly involved outcomes reporting for pediatric T1D populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of higher HbA1c levels among younger age groups have similarly been reported in earlier registry reports. 11,19,20 One of the unique elements in this registry is that each endocrinologist receives a quarterly report outlining their patient populations' achievements in metabolic outcomes, expressed both as means and as centile ranking within the group, along with the proportion using evidence-based cardiovascular disease prevention therapies. In other jurisdictions, 21 quality improvement initiatives have similarly involved outcomes reporting for pediatric T1D populations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the use of thiazolidinediones, the risk of bone fractures in postmenopausal women increases [ 15 ]. Finally, recent studies have observed a marked influence of socioeconomic and psychosocial aspects on glycemic health control and a significant association between sociodemographic profile and absolute control of T1DM risk factors [ 59 , 60 ]. Furthermore, T2DM women and men with lower income and education level show poor food choice revealing higher carbohydrate and lower fat intake.…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 99%
“…The incidence of type 1 diabetes (T1D) has been increasing in Europe and worldwide. The care of patients with T1D has a major economic impact on families and health care systems . The introduction of new technologies enables T1D patients to achieve optimal glycemic control without an increased risk of severe hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…The care of patients with T1D has a major economic impact on families and health care systems. 1 The introduction of new technologies enables T1D patients to achieve optimal glycemic control without an increased risk of severe hypoglycemia. However, not all modern technologies are currently covered even in developed countries, and their accessibility for children with T1D can therefore be considerably limited by the socioeconomic status of the family, type of health insurance of the patient, structure of the health system, This study aimed to evaluate the current situation of reimbursement of insulins, glucometers, insulin pumps (CSII), and continuous glucose monitoring (CGM) devices for children with T1D in European countries participating in the SWEET Project and to compare data from EU countries with the data from our previous study in 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation